DETERMINAN KEJADIAN HIPERTENSI PADA LANSIA - Jonathan Kelabora; Ivonne A.V. Gasper; A. Suyatni Musrah; Herlina Herlina (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: Hypertension is a medical condition characterized by an increase in blood pressure above normal limits in the arteries. The elderly are one of the age groups that are prone to hypertension. The purpose of this study was to determine the determinants of hypertension in the elderly. The study design used in this study was cross-sectional. The study was conducted from April to June 2025 at the Pekauman Community Health Center. The study population consisted of all male individuals aged 36-≥65 years with hypertension who came to the health center for treatment. The sample consisted of 75 respondents. The sampling technique used was purposive sampling. The research instrument used was a research questionnaire. Data analysis was performed using univariate and bivariate methods. The results showed a relationship between smoking behavior (p value: 0.000) and no relationship between stress (p value: 0.067) and the incidence of hypertension in the elderly. It is recommended that the elderly reduce their smoking frequency and control their thoughts to avoid stress that can affect their health, especially an increase in blood pressure.Keywords: Elderly, Hypertension, Smoking Behavior.